PEMASARAN, SIKAP DAN LOYALITAS KONSUMEN AYAM GORENG SAMBAL LADAS MELALUI E-COMMERCE - Rosfenda, Siti Meisa; Indriani, Yaktiworo; Nugraha, Adia (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2025)
This research aims to identify the selected e-commerce platform and assess customer attitudes and loyalty towards the marketing of Ayam Goreng Sambal Ladas (AGSL) products on that platform. This research uses a survey method carried out at the AGSL business center. A total of 75 consumers were selected using purposive techniques and quota sampling. Data was collected between December 2022 and January 2023, then analyzed using descriptive statistics, Fishbein Multiattribute Analysis, and the loyalty pyramid model. Research findings show that Instagram is the platform most frequently used to obtain information because of its up-to-date and clear content, while GoFood is the e-commerce platform most commonly used for purchases because of its more attractive promotions. The consumer attitude score of 348,413 shows a positive attitude in the "like" category. In addition, consumer loyalty calculations reveal that the percentage of committed buyers (78.667%) is higher than switcher buyer (53.333%). Key words:   AGSL, E-Commerce, Fishbein Multiattribute, Loyalty Pyramid